2014
DOI: 10.1016/j.celrep.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interactions between TIP60 and p300 Regulate FOXP3 Function through a Structural Switch Defined by a Single Lysine on TIP60

Abstract: SUMMARY The human FOXP3 molecule is an oligomeric transcriptional factor able to mediate activities that characterize T regulatory cells, a class of lymphocytes central to the regulation of immune responses. The activity of FOXP3 is regulated at the post-translational level, in part by two histone acetyltransferases (HAT), TIP60 and p300. TIP60 and p300 work cooperatively to regulate FOXP3 activity. Initially p300 and TIP60 interactions lead to the activation of TIP60 and facilitate acetylation of K327 of TIP6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 29 publications
5
112
1
Order By: Relevance
“…Since histone H4 acetylation is affected by TIP60 knockdown at all genes analyzed, TIP60 effects could be driven by other acetylation targets in the transcriptional apparatus. In fact, several non-histone TIP60 targets, including transcription factors, have been identified (Patel et al, 2004; Sun et al, 2005; Tang et al, 2006; Tang et al, 2008; Xiao et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Since histone H4 acetylation is affected by TIP60 knockdown at all genes analyzed, TIP60 effects could be driven by other acetylation targets in the transcriptional apparatus. In fact, several non-histone TIP60 targets, including transcription factors, have been identified (Patel et al, 2004; Sun et al, 2005; Tang et al, 2006; Tang et al, 2008; Xiao et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the observation of the y4 ion eliminated the Thr-38 possibility, and the observation of y9 ion further confirmed the phosphorylation at the Ser-33 site. The same approach of using key MS2 spectrum ions was conducted for the phosphorylation site assignments for panels B and C. addition, we have observed that Tip60 and p300 modify distinct residues of the Foxp3 protein (32,33). Dephosphorylation of Ser-418 by PP1 at the C-terminal domain of FOXP3 may negatively regulate Treg cell function (17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, human FOXP3 protein is capable of interacting with the coactivators p300 and TIP60 and such interaction promotes the transcriptional activity of FOXP3, while Treg cell-specific deletion of p300 and TIP60 results in loss of Treg function. 36 In contrast, Foxp3 recruits Eos and the corepressor CtBP1 to repress the expression of genes such as Il2. Since IL-2 repression is critical for Treg cell-mediated immune regulation, silencing Eos in Treg cells abrogates their suppressive function.…”
Section: Foxp3 and Its Cofactorsmentioning
confidence: 97%
“…Some of the proteins currently reported to be capable of interacting with Foxp3 are NFκB, 32 NFAT, 22 Runx1, 28 Eos, CtBP1, 33 CBFb, Gata3, Ash2l, Bcl11b, Ikzf3, Foxp1, Smarcc1, Smarce1, Smarca4, Smarca5, Chd4, Hdac2, Rcor1, Lsd1, 34 HIF-1α, IRF-4, 35 p300, TIP60, 36 and Ezh2. 26 Though Foxp3 is likely to exist in a large protein complex, not all these cofactors are always found in the same complex.…”
Section: Foxp3 and Its Cofactorsmentioning
confidence: 99%